Understanding the Loss of Public Education: A Critical Ecological Perspective on Systemic Challenges in School and Society - Houser, Neil O. (Critical Education)

(untitled) (Institute for Critical Education Studies / UBC, 2023)
The decline of public education and the concomitant loss of the commons are increasingly recognized as significant and interwoven issues. Like other prevailing societal problems, such as the tenacity of institutionalized racism, classism, and patriarchy, these conditions are rooted in the ways growing numbers of people have come to think and act – socially, economically, politically, and intellectually. In a word, they are structural problems. As such, they require educators and others concerned with the health of society and well-being of the planet to address not only the observable symptoms but also the underlying factors that have spawned and perpetuated the systems in the first place. Critical scholars generally understand that problematic structural conditions are produced and maintained by prevailing systems of thought and action, that they evolve within particular social and historical contexts, and that they have often been instituted through oppressive mechanisms of persuasion and control. Less understood are the ways these intersecting systems, contexts, and mechanisms are perpetuated via largely “invisible” perceptual and temporal factors that obscure the processes at play. Understanding the relationships between these various factors is essential to effectively addressing the challenges we face. This paper synthesizes the literature in critical theory, ecological philosophy and living systems theories, Indigenous studies, and the sociology of knowledge to examine these intersecting factors and to consider implications for theory and practice in education.